The Fugitive Underground of British Blackness: Insights from London’s ‘Riotous’ Geographies - Adscheid, Toni (ACME, 2023)
This paper historicizes the riotous geographies of British Blackness by focusing on three so-called “riots” in London’s post-World War II development, the 1958 Notting Hill uprisings, the 1981 Brixton uprisings and the 2011 pan-London uprisings. Mobilizing debates in Black (British) Geographies, I challenge state narrations of these events as illegitimate expressions of Black Britons’ political discontent. Based on archival research, I expose such framings as ongoing attempts of whiteness to render Black British geographies “ungeographic” within a supposed white British geography. Employing fugitivity as method, I show how these riotous events constituted possibilities for escaping racialized spatio-political categories of British state geographies. I consider British Blackness as political category and as a historically contingent discursive construction that mobilizes people from the African diaspora in specific ways but also stretches beyond them. Thus, I ask: How does Blackness continue to escape attempts of capturing it in and through British state geographies and in what ways does this escape constitute a transfiguration of Black British (un)geographies? The three historical cases I examine exemplify the struggles between the state’s efforts to enclose and exclude Black Britons and their efforts to forge an underground of British Blackness in the wake of Empire.